2022
DOI: 10.1021/acs.jafc.2c05925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microbial Action and Moist-Heat Action on the Nonvolatile Components of Pu-Erh Tea, as Revealed by Metabolomics

Abstract: Microbial action and moist-heat action are crucial factors that influence the piling fermentation (PF) of Pu-erh tea. However, their effects on the quality of Pu-erh tea remain unclear. In this study, the effects of spontaneous PF (SPPF) and sterile PF (STPF) on the chemical profile of Pu-erh tea were investigated for the first time, and sun-dried green tea was used as a raw material to determine the factors contributing to the unique quality of Pu-erh tea. The results indicated that the SPPF-processed samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…To summarize, the fermentation of A. luchuensis led to an increase in the levels of soluble sugar, total lignin, total hemicellulose, and monosaccharide, whereas it reduced the amounts of polysaccharide and cell wall cellulose. Previous studies have also reported an increase in the levels of arabinose (Gong et al, 2010), glucose (Wang et al, 2022), mannitol (Zhang et al, 2023), xylitol, sorbitol (Shao et al, 2022), and dulcitol (Li et al, 2022), which is consistent with the findings presented here.…”
Section: Metabolism Of Soluble Sugarssupporting
confidence: 93%
“…To summarize, the fermentation of A. luchuensis led to an increase in the levels of soluble sugar, total lignin, total hemicellulose, and monosaccharide, whereas it reduced the amounts of polysaccharide and cell wall cellulose. Previous studies have also reported an increase in the levels of arabinose (Gong et al, 2010), glucose (Wang et al, 2022), mannitol (Zhang et al, 2023), xylitol, sorbitol (Shao et al, 2022), and dulcitol (Li et al, 2022), which is consistent with the findings presented here.…”
Section: Metabolism Of Soluble Sugarssupporting
confidence: 93%
“…Sample preparation: The raw material of SDGT was provided and processed by Menghai Tea Factory, consistent with the samples used in our previous study ( Li, Zhang, et al, 2022 ; Li et al, 2023 ) ( Fig. 1 a).…”
Section: Methodsmentioning
confidence: 99%
“…1 Analyze the flowchart. (a) Schematic diagram of sample preparation ( Li, Wu, et al, 2022 ; Li, Zhang, et al, 2022 ), (b) Demonstration of tea samples, (c) Comparative descriptive aroma profiles of different tea infusions, (d) Key aroma components in different samples. Note: SDGT, sun-dried green tea; SPPF, spontaneous piling fermentation; and STPF, sterile piling fermentation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations